Development of the analytical component of the Farm level Calculator modules of the ICT-based Smart CSA monitoring App for assessing performance, synergies and trade-offs. - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
All the input variables needed for the calculation of farms' tri- dimensional performance (in terms of Productivity, Adaptation/Resilience and Mitigation) were introduced in the new version of the Geofarmer App and some first equations introduced (costs, benefit, gross margin) to allow automatic calculations. This prototype was tested in Senegal.